Entrepreneurial Ambitions in the Public Sector - Linda A. Renzulli (Arizona State University, 2002)
In this article, I study charter schools as social innovations within the population of established public educational institutions. I begin by briefly outlining the history of public schools in the United States. Organizational theories are applied to explain the perpetuation of the structure of public schools since World War II. Next, I delineate the characteristics of educational reform movements in the United States by focusing on the charter school movement. Then, I use an evolutionary approach to study the environmental characteristics that drive the perceived need for innovation and the promotion of experimentation. Using data compiled from the North Carolina Department of Public Instruction, the Census Bureau, and North Carolina State Data Center, I examine the characteristics of the local environment that promotes the submission of charter school applications in North Carolina over a three-year period, 1996-1998. It is shown that school districts in need of school choice do have a higher mean charter school submission rate. Also, some community characteristics and available resources are important for the initial stage of charter school formation.